Correlation between ultrafiltration rate and hemoglobin level and erythropoietin response in hemodialysis patients - Li Cui; Lili Zhang; Jing Li; Yuan Li; Xiaolei Hao; Yan Xu; Chunmei Li (Renal Failure)
This study aimed to investigate the correlation between ultrafiltration rate (UFR) and hemoglobin levels and erythropoietin (EPO) response in patients receiving maintenance hemodialysis (MHD). 225 MHD patients were divided into three groups according to the UFR: < 10 ml/h/kg, 10–13 ml/h/kg, and >13 ml/h/kg. Clinical parameters and prognosis were compared among the groups. Multiple linear correlation and regression analyses were conducted. SPSS 26.0 (IBM, Chicago, IL, USA) was used to analyze all statistics. The UFR < 10 ml/h/kg group was older than the other groups (p < 0.05). The UFR > 13 ml/h/kg group had the highest SpKt/V (p < 0.05), monthly EPO dose/weight (p < 0.001), and EPO resistance index (p < 0.001), as well as the lowest dry weight (p < 0.001), BMI (p < 0.001), hemoglobin (p < 0.001), hematocrit (p < 0.05), and red blood cell count (p < 0.05). Multiple linear regression analysis showed that sex, dry weight, UFR, calcium, phosphorus, albumin, and C-reactive protein levels were associated with hemoglobin levels. Multivariate logistic regression analysis revealed that a higher UFR was associated with lower hemoglobin levels, while male sex and higher levels of calcium and albumin were associated with higher hemoglobin levels. High UFR is associated with more severe anemia and EPO resistance in MHD. This study provides new insights into anemia management in patients undergoing hemodialysis.